Lower extremity muscle strength reference values for young Saudi male adults aged 21 to 23 years and their correlation with anthropometric parameters and balance - Jaya Shanker Tedla; Devika Rani Sangadala; Ravi Shankar Reddy; Kumar Gular; Venkata Nagaraj Kakaraparthi; Paul Silvian Samuel (Canadian Science Publishing, 2022)
Normative reference values for muscle strength are needed for muscle strength assessment and estimation of prognosis in lower extremity related neuromuscular disorders, as muscle strength influenced by anthropometric parameters and muscle strength itself affects balance. Normative reference values for muscle strength in the Saudi Arabian population is lacking in the literature. Hence, the current study aimed to establish normative reference values for lower extremity muscle strength and to correlate these values with anthropometric parameters and balance. Lower extremity muscle strength and balance were assessed by baseline hand-held dynamometer and by forward, lateral, and oblique direction reach tests in 421 young male adults between 21 and 23 years of age. The mean and standard deviation of lower extremity strength ranged from 43.83 ± 16.92 lb to 62.07 ± 10.74 lb. Body weight, body mass index, and oblique and lateral reach distances were correlated with some knee and ankle muscle strength values. Body weight, body mass index, and balance showed significant effect on lower extremity muscle strength. Furthermore, decreased muscle strength may impair balance; the current clinical practice should evaluate body weight, body mass index, and muscle strength during the assessment process.